Ligninolytic potential of Curvularia kusanoi L7 laccases for animal production - Alberto, Maryen; Valiño, Elaine; Torta, Livio; Laudicina, A.; Mirabile, Giulia (Cuban Journal of Agricultural Science, 2020)
The present research was conducted with the objective of evaluating the ligninolytic potential of Curvularia kusanoi L7 laccases in improving the nutritional quality of fibrous substrates for animal feed. Laccase production was obtained from C. kusanoi L7 under native conditions by solid submerged fermentation of wheat bran and by biological interactions with Trichoderma viride M5-2 and Trichoderma pleuroticola. The enzymes were purified from the culture broths by triphasic partition. The degradative potential of native and induced laccases where evaluated by determining foliar lignololytic capacity, raw wheat (Triticum aestivum) straw delignification and the effect of enzyme pretreatment on fibrous fractionation and in vitro digestibility of sugarcane bagasse. Laccases, both native and induced, presented high foliar degradation and delignification of raw wheat straw. Regarding to the improvement of nutritional quality of sugarcane bagasse, all the enzyme pretreatments managed to decrease the fiber content and increase in vitro digestibility. Compared to untreated bagasse, native laccase pretreatment obtained the highest digestibility values (P<0.05) for dry matter (54.71 %), organic matter (63.14 %), acid detergent fiber (63.59 %) and cellulose (65.46%). It is concluded that C. kusanoi L7 laccases can be used as a novel tool in improving the nutritional quality of fibrous sources for animal feed. Key words: Enzyme, induction, fiber, pretreatment, in vitro digestibility